The scientific information ecosystem: structure and aggregation levels - Abadal, Ernest; Codina, Lluís (Anuario ThinkEPI, 2011)
The structure and characteristics of the main products for accessing scientific information are described. The different types of content, the technology used (assignment and harvesting of metadata, full text indexing, or federated search) and their results are analysed. The products are: bibliographic databases, academic journals portals, repositories, academic search engines, academic metasearch engines, and library metasearch engines.
Keywords: Scientific information; Academic search engines; Repositories; Academic journals portals; Academic metasearch engines; Bibliographic databases; Libraries metasearch engines.